Extracorporeal membrane oxygenation support for right ventricular failure after left ventricular assist device implantation. (16th October 2017) - Riebandt, Julia; Haberl, Thomas; Wiedemann, Dominik; Moayedifar, R; Schloeglhofer, Thomas; Mahr, Stéphane; Dimitrov, Kamen; Angleitner, Philipp; Laufer, Guenther; Zimpfer, Daniel
Abstract: OBJECTIVES: Right ventricular (RV) failure complicating left ventricular assist device implantation is associated with increased mortality. Despite a lack of supporting evidence, venoarterial extracorporeal membrane oxygenation (ECMO) support is increasingly being used as an alternative to traditional temporary RV support. We report our institutional experience with ECMO-facilitated RV support after left ventricular assist device implantation. METHODS: We retrospectively reviewed the concept of temporary ECMO support for perioperative RV failure in 32 consecutive left ventricular assist device (mean age 52 ± 14 years; male 84.4%; ischaemic cardiomyopathy 40.6%; INTERMACS Level I 71.8%; INTERMACS Level II 6.3%; INTERMACS Level III 12.5%; INTERMACS Level IV–VII 9.4%; HeartWare ventricular assist device 75%; HeartMate II: 25%) from May 2009 to April 2014. The study end points were RV recovery during ECMO support, mortality and causes of death. RESULTS: Twenty-nine (90.6%) patients were successfully weaned from ECMO support after RV recovery. Three (9.4%) patients expired during ECMO support. ECMO support improved RV function and haemodynamic parameters (central venous pressure 13 mmHg vs 10 mmHg, P < 0.01; mean pulmonary artery pressure 28 mmHg vs 21 mmHg, P < 0.01; cardiac output 5.1 l/min vs 5.9 l/min, P = 0.09) over a median period of 3 (range 1–15) days. Thirty-day and in-hospital mortality were 18.8% and 25%, respectively. One-year survival was 75%, causes of death were multiorgan dysfunction syndrome (50%), sepsis (25%), haemorrhagic stroke (12.5%) and ischaemic stroke (12.5%). Causes of death during ECMO support were ischaemic stroke, sepsis and multiorgan dysfunction syndrome. CONCLUSIONS: Temporary ECMO-facilitated RV support is associated with good long-term outcomes and high rates of RV recovery.